Comparative cytogenetics of Hemorrhois hippocrepis and Malpolon monspessulanus highlights divergent karyotypes in Colubridae and Psammophiidae (Squamata: Serpentes) - M. Mezzasalma; E. Brunelli; G. Odierna; F. M. Guarino (The European Zoological Journal, 2023)
AbstractDespite the growing interest in the evolutionary cytogenetics of squamates, chromosomal data are lacking for most taxa. We performed a preliminary molecular taxonomic analysis and a comparative cytogenetic study on Hemorrhois hippocrepis and Malpolon monspessulanus. We used a combination of standard karyotyping, Chromomycin A3/Methyl green staining, C-banding, Ag-NOR staining and NOR-FISH to provide the first karyotype description of H. hippocrepis and a re-description of the karyotype of M. monspessulanus, including chromosome markers, heterochromatin patterns and sex chromosome systems. Our results show that H. hippocrepis has 2 n = 36 chromosomes, with 16 macro- and 20 microchromosomes and NORs on the 6th pair. The 4th pair represents homomorphic (metacentric) ZW sex chromosomes, but the W chromosome is completely heterochromatic. Malpolon monspessulanus has 2 n = 44 chromosomes, with 20 macro- and 24 microchromosomes, NORs on the 6th telocentric pair. The 4th pair represents the sex chromosomes (ZZ/ZW), with a W chromosome smaller than the Z and completely heterochromatic. Comparing our cytogenetic data to those available from the literature, we note the occurrence and distribution of primitive and derived chromosomal characteristics and discuss the chromosome diversification in two snake clades belonging to Colubridae and Psammophiidae, respectively. We highlight that these two families followed different chromosome diversification pathways, characterised by a highly conserved karyotype structure in Colubridae and a higher chromosome variability in Psammophiidae, mostly driven by a progressive reduction of the chromosome number by means of chromosome fusions. We also provide cytotaxonomic insights supporting the distinction between M. monspessulanus and M. insignitus.